Mathematical problem-solving ability of Information Technology Faculty students through a realistic approach - Puspitasari, Wahyu Dwi; Febrinita, Filda; Rahma, Ika Ayu Nur (Psychology, Evaluation, and Technology in Educational Research, 2024)
Computer Systems study program students have a low understanding of the material. The mid-term and final exam scores show the level of students' understanding is still low. In addition, the results of previous research also show that students have difficulty completing mathematical calculations. The purpose of this study is to describe students' problem-solving abilities. The research method used is the descriptive method. The instrument used for data collection was a problem-solving ability question developed with a realistic approach. Three validators have validated this problem-solving question, and small-scale testing has stated that the results are valid and reliable. The study results show that 35.71% of students got a good category, 28.57% got the sufficient category, 7.15% got a less category, and 28.57% got the very less category. Aspects of problem-solving abilities that still need to be improved are planning problem-solving, solving problems according to plan, and re-checking the procedures and results of the solution. From the results of this study, applying the problem-solving learning model with a realistic approach to improve students' problem-solving abilities can be done for further research.